Eksplorasi Sains melalui Game Interaktif di SDN Roja 1: Pengabdian - Tryani, Agus; Wea, Arminda Yuliana; Sariyyah, Nining; Ali, Jamila H.; Gerhana, Imam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Student Creativity Program (PKM) aims to explore the application of interactive games in science learning at SDN Roja 1 and to examine their impact on students’ interest and understanding. The implementation of interactive games in science learning shows that students are able to increase active engagement, foster learning motivation, and better understand scientific concepts in a more concrete and enjoyable way. Furthermore, game-based learning encourages positive attitudes among students, such as cooperation, curiosity, and self-confidence in the learning process. Therefore, interactive games can be considered an effective alternative learning medium for science education in elementary schools.